Feasibility of screening for critical congenital heart disease using pulse oximetry in Indonesia - Murni, Indah K. (BioMed Central Ltd, 2022)
Background: Screening of critical congenital heart disease (CCHD) using pulse oximetry is a routine procedure in many countries, but not in Indonesia. This study aimed to evaluate the feasibility of implementing CCHD screening with pulse oximetry for newborns in Yogyakarta, Indonesia. Methods: A cross-sectional study was conducted at four hospitals in Yogyakarta, Indonesia. Newborns aged 24–48 hours who met the inclusion criteria were screened on the right hand and left or right foot using a pulse oximeter. Positive results were indicated by: either (1) SpO2 level < 90% in one extremity, (2) SpO2 level of 90–94% in both right hand and either foot on three measurements conducted 1 hour apart, or (3) a saturation difference > 3% between the upper and lower extremity on three measurements conducted 1 hour apart. Positive findings were confirmed by echocardiography. Results: Of 1452 newborns eligible for screening, 10 had positive results and were referred for echocardiographic evaluation. Of those, 8 (6 per 1000 live birth, 8/1452) had CCHD. Barriers found during screening processes were associated with hospital procedures, equipment, healthcare personnel, and condition of the newborn. Conclusion: Pulse oximetry screening might be feasible to be implemented within the routine newborn care setting for CCHD in Indonesia. In order to successfully implement pulse oximetry screening to identify CCHD in Indonesia, the barriers will need to be addressed.